2021
DOI: 10.1080/03949370.2020.1870571
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochrome 1a localisation in light- and dark-adapted retinae of several migratory and non-migratory bird species: no signs of light-dependent activation

Abstract: The magnetic compass of birds seems to be based on light-dependent radical-pair processes in the eyes. Cryptochromes are currently the only candidate proteins known in vertebrates that may serve as the primary radical-pair-based magnetoreceptor molecules. Previous immunohistochemical studies have suggested that cryptochrome 1a (Cry1a) is localised in the photoreceptor outer segments of the ultraviolet/violet (UV/V) cones, and it has been claimed that differences in Cry1a antibody staining intensities show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 87 publications
3
35
0
Order By: Relevance
“…When we started the current study, no isoforms of CRY1 were known for the zebra finch, which is why we make no differentiation between CRY1 and CRY1a throughout the text. Nevertheless, the alignment clearly shows that the detected epitope corresponds to the CRY1a isoform, as is also the case for the protein detected by Niessner 26 , 27 , 56 , and Bolte 44 .…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…When we started the current study, no isoforms of CRY1 were known for the zebra finch, which is why we make no differentiation between CRY1 and CRY1a throughout the text. Nevertheless, the alignment clearly shows that the detected epitope corresponds to the CRY1a isoform, as is also the case for the protein detected by Niessner 26 , 27 , 56 , and Bolte 44 .…”
Section: Resultssupporting
confidence: 58%
“…It is worth mentioning that during the revision of this manuscript, Bolte el at . 44 confirmed that CRY1a is present in the outer segments of UV cones in European robins, Eurasian blackcaps ( Sylvia atricapilla ) and domestic chickens, using an antibody directed against the same target as Niessner et al 26 . However, contrary to Niessner et al .…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations